Paretage Assigment Gene Expressio Of Growth Related Gene In Snakehead Murrel, Channa Striata - Fong, Pooi Har (2020)
Haruan (Channa striata) is a fresh water fish known for its medicinal value and is an important source of protein in Southeast Asia. The demand for this fish is still high; hence this species has good market potential for aquaculture industry in Malaysia. Furthermore, snakehead farming is not popular and there is yet a selective breeding as well as systematic hatchery programmes developed in Malaysia. Hence, the first objective of this study was to investigate the feasibility of using the existing microsatellite markers in genotyping C. striata for parentage identification and pedigree management. The next objective is to establish a reference for transcriptome library for gene expression study. With the transcriptome library, differentially expressed genes in response of fast and slow growth could be identified and applied in snakehead murrel selective breeding programmes. Accurate parentage identification for pedigree management is integral to a successful systematic hatchery programme especially in aquaculture industry to prevent inbreeding depression. Hence, the feasibility of seven pairs of microsatellite markers characterized previously for a population genetics study of C. striata was evaluated in this study. A total of 211 offspring from 22 brood stocks kept in six separated tanks were genotyped according to tanks and were later assigned back to these 22 brood stocks using five different parentage assignment software. Among these software, Colony was the best software to successfully allocate the offspring back to their parents. In addition, the results of the parentage allocations revealed that mating behaviour of this species is polygamous and polyandry.